Architectures of asylum: Making home in a state of permanent temporariness - Steigemann, Anna Marie; Misselwitz, Philipp (Current sociology, 2020)
Urban research in Germany has started to address the socio-spatial distribution and architectures of so-called collective accommodation for asylum seekers, refugee camps, and new forms of ethnic segregation triggered by refugee movements in recent years. The spatial practices of refugees themselves within these processes have not yet been a subject of substantive research. Combining research methods from social and architectural sciences, this article investigates the physical, material, social and symbolic appropriation processes and the spatial dimension of homemaking by Syrian refugees currently housed in refugee accommodation in Berlin, Germany. What spatial knowledge is mobilized at the place of asylum in order to turn the accommodation into a home? How do spatial practices and knowledge hybridize practices of the place of origin, experiences made during the flight and the arriving and uncertain period of stay at an unfamiliar place of asylum? How do spatial appropriation processes collide with humanitarian logics and technocratic emergency management approaches at the place of asylum? With these questions, the article focuses on the ways in which refugees perceive, adapt to, appropriate and alter their new urban environment physically and socially, and how they thereby draw on existing and evolving stocks of urban knowledge, urban experiences and social relationships. It argues that to develop a homelike space in temporary accommodation, arriving refugees mobilize knowledge at the place of asylum which can only be understood as a re-figuration process that is equally at work in the case of other migrants, migration and translocal processes. Studying these urban re-figurations thus helps us to reveal how the interplay of refugees’ agency and their knowledge and the technocratic regime – as a state of permanent temporariness – affects the making of a ‘home’.